2015
DOI: 10.1371/journal.pone.0120509
|View full text |Cite
|
Sign up to set email alerts
|

Lipid from Infective L. donovani Regulates Acute Myeloid Cell Growth via Mitochondria Dependent MAPK Pathway

Abstract: The microbial source, which includes live, attenuated, or genetically modified microbes or their cellular component(s) or metabolites, has gained increasing significance for therapeutic intervention against several pathophysiological conditions of disease including leukemia, which remains an incurable disease till now despite recent advances in the medical sciences. We therefore took up the present study to explore if the leishmanial lipid (pLLD) isolated from L. donovani can play an anti-neoplastic role in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…It was well known that Bcl2 inhibits Beclin1-dependent autophagy by interacting with the evolutionarily conserved autophagy-related protein Beclin1 in yeast and mammalian cells [27]. It was reported that the phosphorylation of ERK1/2 is associated with the high expression of Bcl2 [28]. Here, we found that TGF-β1 enhanced the expression of Bcl2 maybe through the ERK1/2 signal pathway.…”
Section: Autophagy-related Target Of Mir-449amentioning
confidence: 48%
“…It was well known that Bcl2 inhibits Beclin1-dependent autophagy by interacting with the evolutionarily conserved autophagy-related protein Beclin1 in yeast and mammalian cells [27]. It was reported that the phosphorylation of ERK1/2 is associated with the high expression of Bcl2 [28]. Here, we found that TGF-β1 enhanced the expression of Bcl2 maybe through the ERK1/2 signal pathway.…”
Section: Autophagy-related Target Of Mir-449amentioning
confidence: 48%
“…MAPKs, also known as extracellular signalregulated kinases (ERKs), are highly conserved molecules regulating various extracellular and intracellular signalling pathways [9]. Three subfamilies of MAPK including ERK1/2, JNK, and p38 kinase are associated with the regulation of many physiopathological processes, such as apoptosis, differentiation, and senescence [9]. ROS acts as a common and important modulator of many cellular signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…ROS acts as a common and important modulator of many cellular signalling pathways. It is known to activate several MAPKs, which can thus induce apoptosis in response to cellular oxidative stress [9]. Mitochondria are the main sources of ROS, generated specifically by complexes I and III of the respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their functions have remained highly evolutionarily conserved (18). MAPK1, also known as ERK2, is a ~42 kD protein and is mediates one of the most important signaling pathways in vivo, with a crucial role in cell growth, differentiation, proliferation, survival and in the inflammatory response (19). A previous study reported that the MAPK1 signaling pathway is crucial in most cells and is regulated at numerous levels.…”
Section: Introductionmentioning
confidence: 99%